Birthplace of Marx in Trier, Brückenstrasse. Inspriction above the entrance door: "restauriert 1947" - Besselsen, Piet
Birthplace of Marx in Trier, Brückenstrasse. Inspriction above the entrance door: "restauriert 1947".